KEBIJAKAN PEMBELAJARAN MKWK BAHASA INDONESIA DI PERGURUAN TINGGI: IMPLEMENTASI DAN TANTANGANNYA - Muhammad Zulfadhli; Dadang S. Anshori; Dadang Sunendar (STKIP Siliwangi, 2023)
The globalization era has had an impact on the existence of the Indonesian language. Responding to this issue, Indonesian language is important to learn through the education level in Indonesia. This study aims to describe the content, implementation, and challenges of the compulsory curriculum course Indonesian language learning policy in tertiary institutions. This research method used a literature review sourced by policy documents and scientific journal articles. The results showed that the Indonesian language learning policy was released by the government of the Republic of Indonesia in various regulations contained in Law Number 12 of 2012, Government Regulation Number 57 of 2021, and Decree of the Director General of Higher Education Ministry of Education and Culture of the Republic of Indonesia Number 84/E/KPT /2020. The existence of this policy provides an overview of the standard of learning Indonesian language in higher education. Generally, policies regarding learning Indonesian language in higher education have been implemented, although there are still various obstacles. The challenges of the implementation include advances in technological development, student language mastery, and digital-based learning components. The involvement of various parties is needed in order to achieve the expected policy objectives.